Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.